(untitled) (Archaeologia Adriatica, 2025)
Based on data collected over the past three decades, the paper presents a topographic picture of the geographical area of Vinkovci during the course of the Sopot culture. With the aim of obtaining land-use patterns in the landscape for this period, sites/ settlements have been topographically analysed to determine and describe their size, architecture and spatial organisation. The results of archaeological excavations reveal a complex network of densely populated places. The area is extremely important for an understanding of the infrastructural and material heritage of the Sopot culture over the course of its duration from the late 6th and during the 5th millennia BC.